Nurse managers’ views regarding patients’ long waiting time at community health centers in Gauteng Province, South Africa - Solly Ratsietsi Makua; Sisinyana Khunou (Belitung Nursing Journal, 2022)
Background: Patients’ long waiting time still exceeds the set target of 120 minutes. As a result, the volume of complaints remains a concern that points to systems inefficiencies. Minimal attention has been given to the experiences of nurse managers regarding patients’ long waiting time Objective: To explore and describe the experiences of nurse managers regarding patients’ long waiting time at Community Health Centers (CHCs) in Gauteng Province, South Africa Methods: The research applied qualitative exploratory descriptive and contextual design. Non-probability purposive sampling techniques were used to select eight nurse managers. Individual semi-structured interviews were conducted and captured with an audio tape. Tesch’s 8-steps of data analysis were followed to analyze the data. Results: Three themes and seven categories emerged from the study: (1) The adverse effects of patients’ long waiting time (early birds to evade long queues, increased patients’ complaints and compromised quality care), (2) Factors that contribute to patients’ long waiting time (records and patient administration system deficiencies, poor time management, patients’ lack of adherence to booking system), (3) Measures to mitigate patients’ long waiting time (embracing decongestion systems to mitigate patients’ overflow at CHC). Conclusion:  The study recommends the optimal implementation of an appointment system to avert long waiting times. Collaboration between CHCs’ management and clinic committees is encouraged to provide the best solutions to the reduction of patients’ long waiting times. In addition, time management is one area that needs to be improved. A digital record management system can assist in better-sought problems related to filling. Studies are encouraged on a model to enhance collaboration in reduction of patients’ long waiting time.